An Efficient Synthesis of Azetidines with (2-Bromoethyl)sulfonium Triflate - Fritz, Sven P.; Moya, Juan F.; Unthank, Matthew G.; McGarrigle, Eoghan M.; Aggarwal, Varinder K. (Synthesis, 2012)
Easily accessible arylglycine derivatives were cyclized to azetidines by using commercially available (2-bromoethyl)sulfonium triflate in a simple and mild procedure. The high-yielding reaction has a relatively broad scope and was extended to the synthesis of an oxetane.
Keywords: annulations; cyclizations; heterocycles; sulfur; ylides